Septic arthritis in the pediatric hip joint: a systematic review of diagnosis, management, and outcomes - Nannini, Alessandra; Giorgino, Riccardo; Bianco Prevot, Luca; Bobba, Andrea; Curci, Domenico; Cecchinato, Riccardo; Peretti, Giuseppe M.; Verdoni, Fabio; Mangiavini, Laura (Frontiers in Pediatrics, 2023)
Septic arthritis of the pediatric hip joint (SAH) is a rare but serious orthopedic emergency requiring immediate diagnosis and management. Delayed recognition can lead to severe complications, emphasizing the need for timely intervention. This systematic review aims to provide a comprehensive analysis of SAH in the pediatric population, focusing on its diagnosis, management, and outcomes. The review included 11 studies involving 391 patients with SAH, aged between three months and 12 years. Staphylococcus aureus was identified as the most common causative pathogen, with increasing cases of methicillin-resistant strains. Diagnosis is challenging due to nonspecific clinical presentations, necessitating validated criteria and a multidisciplinary approach. Ultrasound emerged as a valuable tool for early detection, and MRI was used in challenging cases. Treatment options include hip aspiration, arthrotomy, and arthroscopy, often combined with appropriate antibiotic therapy. Success rates were comparable among different surgical procedures. Early intervention is vital for optimal outcomes. However, the review highlights the need for standardized protocols and further prospective studies to address limitations and improve understanding and management of SAH in the pediatric hip joint.